Основы технологии тонких и толстых пленок: 23.03 : учеб. пособие / А. Т. Мельниченко - Мельниченко А. Т. (ЛЭИС, 1989)
Экземпляры: КХ (20081114) / Инвентарный номер: 946367 / Цена: 0.75 / Сис.шифр: 22.36 / Авт.знак: М 48 / ГРНТИ: 29 / ББК: 22.36